3D Printing in Dental Science - Cruz Olivo, Edison Andrés (Revista Estomatología, 2022)
3D printing is a technology that describes a manufacturing process previously planned and designed in a computer to create an object 1,2. This technology was introduced in dentistry by Chuck Hull since 1986 and allowed the automation and thus improved dental workflow 2. Technologies used in 3D printing involves: Stereolithography (SLA), bioprinting, fused deposition modeling (FDM), selective laser sintering (SLS), and PolyJet printing. We can choose one of them depending on the clinical use and material, need of accuracy among others. To 3D printing you need to use a scanner with an integrated software in order to capture the 3D images of the object being scanned. Those 3D images are stored in Standard Tessellation Language (STL) file 3. But what “Tessellation” means? Tessellation is the covering process of a surface, using one or more geometric shapes, with no overlaps and no gaps. It means that the object scanned is copied in detail with high reliability and then can be printed. Before printing, the software cuts the STL file into multiple horizontal layers and creates the G-code for the machine command for the printer. Thus, the resolution of the printer is determined by its layer thickness (z-axis) which represents the vertical accuracy of 3D printer 1. There are two approaches used to fabricate 3D objects: subtractive approach (milling); additive approach (layered manufacturing) 4 . The first, normally use a small model or block to machining it and is indicated to fabricate ceramic crowns in dentistry. The last, can produce complex structures and thus is suitable for reproduce the anatomy of different structures of oral cavity 4.